Celebrity Worship di Kalangan Emerging Adulthood: Peran Self-Esteem dan Psychological Well Being pada Penggemar K-Pop - Dena Nur Arfa; Puspa Rahayu Utami Rahman; Regi Ramadan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Celebrity worship is an abnormal relationship between fans and their idols, characterized by emotional attachment and excessive behavior. The purpose of this study is to determine the influence of self-esteem and psychological well-being on entertainment-social, intense-personal-feeling, and borderline pathological celebrity worship among emerging adult K-Pop fans. The study employs a quantitative method. The population consists of young adults aged 18–25 years in Purwakarta, Subang, and Karawang. The sampling technique used is purposive sampling. Data were analyzed using SPSS version 25.0. The number of respondents in this study was 204. The measurement tools used were the Celebrity Attitude Scale (CAS), Rosernberg Self-Esteem Scale (RSES), and Ryff Psychological Well-Being Scale (RPWBS). The results of the multiple regression analysis showed a significance value of 0.000 (<0.05), indicating that self-esteem and psychological well-being significantly influence celebrity worship entertainment-social, intense-personal-feeling, and borderline-pathological simultaneously. However, when analyzed partially, they were found to influence celebrity worship entertainment-social but not celebrity worship intense-personal-feeling and borderline-pathological. The results of the determination test on self-esteem and psychological well-being toward celebrity worship entertainment-social showed an R Square value of 27.5% with effective contribution values of 1.96% and 25.60%, furthermore, for self-esteem and psychological well-being on celebrity worship intense-personal-feeling, the R Square value was 19.8% with effective contribution values of 0.65% and 19.09%, and for self-esteem and psychological well-being on celebrity worship borderline pathological, the R Square value was 13% with effective contribution values of 1.05% and 12.95%.